2013
DOI: 10.1159/000348868
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Oriented Recovery Enhancement Reduces Pain Attentional Bias in Chronic Pain Patients

Abstract: Background: Chronic pain involves hypervigilance for pain-related stimuli. Selective attention to pain-related stimuli, known as pain attentional bias (AB), can exacerbate chronic pain, prolong suffering, and undermine quality of life. The aim of this study was to determine if a multimodal mindfulness-oriented intervention could significantly reduce pain AB among chronic pain patients receiving opioid analgesics. Methods: A total of 67 chronic pain patients were randomized to an 8-week Mindfulness-Oriented Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 44 publications
1
131
0
2
Order By: Relevance
“…A recent adaptation of an intervention originally developed to treat addiction, Mindfulness-Oriented Recovery Enhancement (MORE)(101), unites complementary aspects of mindfulness training, cognitive reappraisal, and positive psychological principles into an integrative treatment strategy designed to disrupt the cycle of somatic distress and maladaptive cognitive-affective states common to chronic pain. MORE aims to directly stimulate PA by promoting savoring of natural rewards.…”
Section: Conceptual Model For Pa Enhancement In Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent adaptation of an intervention originally developed to treat addiction, Mindfulness-Oriented Recovery Enhancement (MORE)(101), unites complementary aspects of mindfulness training, cognitive reappraisal, and positive psychological principles into an integrative treatment strategy designed to disrupt the cycle of somatic distress and maladaptive cognitive-affective states common to chronic pain. MORE aims to directly stimulate PA by promoting savoring of natural rewards.…”
Section: Conceptual Model For Pa Enhancement In Chronic Painmentioning
confidence: 99%
“…MORE aims to directly stimulate PA by promoting savoring of natural rewards. Evidence from an early stage RCT involving chronic pain patients suggests that MORE may be efficacious for diminishing pain attentional bias and enhancing perceived control over pain (101). Recent findings from this preliminary trial suggest that MORE decreases pain severity and functional impairment (102), and reduces desire for opioid analgesics by enhancing autonomic responsiveness to positive emotional stimuli (102).…”
Section: Conceptual Model For Pa Enhancement In Chronic Painmentioning
confidence: 99%
“…Mindfulness interventions are reportedly associated with reduced attention bias, especially in response to negative stimuli (57,58). However, instability on negative events is not enough to promote well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MORE significantly decreased opioid craving and the risk of opioid misuse by at post-treatment. Subsequent analyses of neurocognitive data from the trial revealed several of MORE's potential mechanisms of action; MORE reduced hypervigilance toward pain-related information (pain attentional bias) [65], decreased subjective opioid cue reactivity [66] and enhanced autonomic nervous system responses to images representing natural rewards (e.g., photos of a sunset, romantic couples, smiling babies, etc.,) [66].…”
Section: Biopsychosocial Mechanisms That Undergird Chronic Pain and Incmentioning
confidence: 99%